Serodiagnosis of Borrelia miyamotoi disease by measuring antibodies against GlpQ and variable major proteins. (December 2018) - Koetsveld, J.; Kolyasnikova, N.M.; Wagemakers, A.; Stukolova, O.A.; Hoornstra, D.; Sarksyan, D.S.; Toporkova, M.G.; Henningsson, A.J.; Hvidsten, D.; Ang, W.; Dessau, R.; Platonov, A.E.; et al.
Abstract: Objectives: Borrelia miyamotoi disease (BMD) is an emerging tick-borne disease in the Northern hemisphere. Serodiagnosis by measuring antibodies against glycerophosphodiester-phosphodiesterase (GlpQ) has been performed experimentally but has not been extensively clinically validated. Because we had previously shown the differential expression of antigenic variable major proteins (Vmps) in B. miyamotoi, our aim was to study antibody responses against GlpQ and Vmps in PCR-proven BMD patients and controls. Methods: We assessed seroreactivity against GlpQ and four Vmps in a well-described, longitudinal cohort of sera from BMD patients ( n =182), healthy blood donors ( n =136) and controls ( n =68). All samples were tested by ELISA and positive sera were tested by western blot, and antibody dynamics and diagnostic value were assessed. Results: IgM antibodies against GlpQ and Vmps peaked between 11 and 20 days, and IgG between 21 and 50 days, after disease onset. Various combinations of GlpQ and Vmps increased sensitivity and/or specificity compared to single antigens. Notably, the GlpQ or variable large protein (Vlp)-15/16 combination yielded a sensitivity of 94.7% (95% CI: 75.4–99.7) 11–20 days after disease onset and a specificity of 96.6% (92.7–98.4) for IgM. A specificity of 100% (97.8–100) for IgM, and 98.3% for IgG (95.2-100), was found when positivity was defined as reactivity to GlpQ and any Vmp, with maximum sensitivities of 79% (56.7–91.5) for IgM and 86.7% (62.1–97.6) for IgG. Conclusions: We clearly demonstrate here the diagnostic potential of these seromarkers. Our findings will facilitate future epidemiological and clinical studies on BMD and lead to the development of a serologic test to be used in clinical practice.